From Farm to Flight: CoverCress as a Low Carbon Intensity Cash Cover Crop for Sustainable Aviation Fuel Production. A Review of Progress Towards Commercialization - Phippen, Winthrop B.; Rhykerd, Rob; Sedbrook, John C.; Handel, Cristine; Csonka, Steve (Frontiers in Energy Research, 2022)
Thlaspi arvense L. (Field Pennycress; pennycress) is being domesticated into a winter-annual oilseed crop that confers cover crop benefits when grown throughout the 30 million-acre U.S. Midwest. Off-season integration of pennycress into existing corn and soybean acres would extend the growing season on established croplands and avoid displacement of food crops or ecosystems while yielding up to 2 billion gallons of seed oil annually. The aviation sector is committed to carbon-neutral growth and reducing emissions of its global market, which in 2019 approached 27 billion gallons of consumption in the U.S. and 100 billion gallons globally. Pennycress seed oil is ideally suited as a new bioenergy feedstock for the production of drop-in Sustainable Aviation Fuel (SAF), biodiesel, renewable diesel, and other value-added coproducts. Through a combination of breeding and genomics-enabled mutagenesis approaches, considerable progress has been made in genetically improving yield and other agronomic traits. With USDA-NIFA funding and continued public and private investments, improvements to pennycress germplasm and agronomic practices suggest that field-scale production can surpass 1,680 kg ha-1 (1,500 lbs ac-1) in the near term. At current commodity prices, our economic modeling predicts this level of production can be profitable across the entire supply chain. Two-thirds of the grain value is in oil converted to fuels and chemicals, and the other one-third is in seedcake used as an animal feed or for industrial applications. In addition to strengthening rural communities by providing income to farmers and agribusinesses, pennycress potentially offers a myriad ecosystem services. The most notable services are water quality protection through reduced nutrient leaching and reduced soil erosion and biodiversity enhancement by supporting pollinators’ health. While the efforts described herein are focused on the U.S., pennycress will likely have a broader application to regions around the world with similar agronomic and environmental conditions.